Assistance for Community Engagement in The Development Of Al-Qur'An Learning Culture in The Nagari Bukit Sileh Solok District - Aris, Sarmen; Habibah, Sariyun; Putri, Shandrella (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The purpose of this service is to increase community literacy in the Al-Qur'an. The ABCD (Asset Based Community Driven Development) strategy is the technique employed. It was discovered that there are still not enough people available, particularly for those who teach the QurÔÇÖan. These restrictions include things like instructing pupils without a specified curriculum. Additionally, the honorarium paid to instructors is still below the legal minimum wage. This is so that parents of students can contribute to the honorarium. The ability to read and write the Koran is something that parents genuinely want for their children, though. Gave aid to instructors in creating curricula and effective learning techniques for the Holy QurÔÇÖan.